2019
DOI: 10.3390/cancers11091354
|View full text |Cite
|
Sign up to set email alerts
|

Purine-Metabolising Enzymes and Apoptosis in Cancer

Abstract: The enzymes of both de novo and salvage pathways for purine nucleotide synthesis are regulated to meet the demand of nucleic acid precursors during proliferation. Among them, the salvage pathway enzymes seem to play the key role in replenishing the purine pool in dividing and tumour cells that require a greater amount of nucleotides. An imbalance in the purine pools is fundamental not only for preventing cell proliferation, but also, in many cases, to promote apoptosis. It is known that tumour cells harbour se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 211 publications
(258 reference statements)
0
49
0
3
Order By: Relevance
“…To examine other potential mechanisms, we performed immunoprecipitation (IP) with the ARL13B antibody, followed by liquid chromatography-mass spectrometry (LC-MS). This analysis identified inosine monophosphate dehydrogenase 2 (IMPDH2), a key ratelimiting enzyme for purine biosynthesis 44,45 , as a novel interacting partner of ARL13B ( Fig. 4D; p<.0001 calculated by Scaffold Viewer software n=2 replicates).…”
Section: Impdh2 Interacts With Arl13b During Tmz Therapy In Pdx Gbm Mmentioning
confidence: 99%
“…To examine other potential mechanisms, we performed immunoprecipitation (IP) with the ARL13B antibody, followed by liquid chromatography-mass spectrometry (LC-MS). This analysis identified inosine monophosphate dehydrogenase 2 (IMPDH2), a key ratelimiting enzyme for purine biosynthesis 44,45 , as a novel interacting partner of ARL13B ( Fig. 4D; p<.0001 calculated by Scaffold Viewer software n=2 replicates).…”
Section: Impdh2 Interacts With Arl13b During Tmz Therapy In Pdx Gbm Mmentioning
confidence: 99%
“…In addition, other studies showed that guanosine would also modulate glutamate transporter activity and that guanine nucleotides are able to displace glutamate from its receptors [32]. As postulated by Tasca et al (2018), "the identification of the extracellular actions of GBPs as intercellular messengers was possible due to five pieces of evidences: (1) GBPs can be found in the extracellular space, where they are released upon certain harmful conditions; (2) hydrolization of extracellular guanine nucleotides leads to the formation of guanosine and guanine; (3) GTP is stored in synaptic vesicles; (4) glutamate binding is displaced by guanine nucleotides; and (5) GBPs modulate glutamate transporter activity. Based on these findings, it can be concluded that GBPs act as endogenous modulators of glutamatergic transmission, and it might result in the potentially critical role that these molecules play in neuroprotection."…”
Section: Specific Effects Of Gbps In Nervous Tissuementioning
confidence: 95%
“…Purines are endogenous organic molecules that are essential for all cells. Purines, adenine-based purines (ABPs) and guanine-based purines (GBPs), are composed of two fused linked rings containing five carbon and four nitrogen atoms as well as their derivatives: nucleosides (nitrogenous bases plus a pentose sugar, commonly ribose); and nucleotides (nitrogenous bases plus ribose and phosphate) that are mono-, di-or tri-phosphorylated [1]. Adenine and guanine are very commonly found in nature, mostly as nucleoside and nucleotide derivatives, i.e., phosphorylates (Adenosine monophosphate, AMP; Adenosine diphosphate ADP; Adenosine triphosphate, ATP; Guanosine monophosphate, GMP; Guanosine diphosphate, GDP; Guanosine triphosphate, GTP).…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations